2015
DOI: 10.1002/jmv.24172
|View full text |Cite
|
Sign up to set email alerts
|

Presence of herpesvirus DNA in cerebrospinal fluid of patients with tick-borne encephalitis and enteroviral meningoencephalitis

Abstract: Reactivation of HHVs in the CNS due to inflammation has not been well described yet. The primary aim of this study was to investigate the frequency of HHV DNA detection in the cerebrospinal fluid (CSF) of immunocompetent patients with meningoencephalitis of other than HHV origin. The secondary aim of this study was to evaluate the impact of herpesvirus co-infection on the clinical course and patient outcome. Ninety-six patients with clinically and laboratory proven tick-borne encephalitis (TBE) and 77 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…TBE occurs at a different age and often leads to meningoencephalitis. TBE positive patients often had leukocytosis in peripheral blood and symptoms lasted longer, as shown in previous studies .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…TBE occurs at a different age and often leads to meningoencephalitis. TBE positive patients often had leukocytosis in peripheral blood and symptoms lasted longer, as shown in previous studies .…”
Section: Discussionsupporting
confidence: 80%
“…TBE occurs at a different age and often leads to meningoencephalitis. TBE positive patients often had leukocytosis in peripheral blood and symptoms lasted longer, as shown in previous studies [15]. In other studies HHV-6 has been observed as the causative agent in 1.75% of CNS infections [16].…”
Section: Discussionsupporting
confidence: 69%
“…It has been reported that herpes virus DNA was detected in CSF of some patients with confirmed enterovirus meningitis [10]. However, the occurrence of coinfection of herpes viruses and enteroviruses in CNS seems to be a rather rare event in immunocompetent patients.…”
Section: Methodsmentioning
confidence: 99%
“…Beside the probable useless administration of Acyclovir following a false positive HSV-1 result, one should also consider the questionable relevance of Herpesviridae detection in CSF in general. As these viruses feature life-long latency after primary infection, subclinical reactivation with replication can be seen in conjunction with different underlying clinical conditions [43,44]. Thus, in a worst case scenario, Herpesviridae detection in multiplex PCR testing might lead to delayed diagnosis of the actual underlying disease, as described by Gomez et al for a patient suffering from tuberculous meningitis [14].…”
Section: Discussionmentioning
confidence: 99%